Iguanian species-richness in the Andes of boreal Patagonia: Evidence for an additional new Liolaemus lizard from Argentina lacking precloacal glands (Iguania, Liolaeminae). - Pincheira Donoso, Daniel (2007)
Most Liolaemus lizard species are characterized by the presence of precloacal glands in males. Only a few taxa lack these sexual signal emitter structures. Phylogenetic evidence suggests that those species are restricted to the clades chiliensis and lineomaculatus. Within the first lineage, L. coeruleus, L. cristiani, L. flavipiceus, L. neuquensis and L. thermarum lack precloacal glands, which have been considered as members of the neuquensis group. Whereas, in the second one, L. periglacialis (=L. hatcheri), L. kolengh, L. lineomaculatus an L. silvanae exhibit this characteristic. In the present study we provide the description of Liolaemus tregenzai, an additional new species lacking precloacal glands in both sexes. This new taxon, member of the chiliensis clade, is so far known from Copahue Volcano, Neuquén Province of Argentina, in boreal Patagonia. Liolaemus tregenzai differs from the remaining species of this clade in having a unique combination of morphologic and chromatic traits, such as a large body size, olive or chest-nut dorsal ground colour, with dark brown or blackish pigment on the flanks, green-bluish with intense black pigment on the ventral surface, and evident sexual dichromatism. The ecology of this new lizard is also remarkably, occurring in Andean antarctandic forests, and being common near thawing snows. Phylogenetic relationships with other members of the chiliensis clade and with the taxa recognized as members of the neuquensis group are still unknown.